The Silent Invasion of Intelligent Technology. A Rereading of "Los caballos de Abdera" by L. Lugones - Esparza, Gustavo; Bravo, Nassim (Amaltea. Revista de Mitocrítica, 2020)
In this paper, the epistemological boundaries between myth and science fiction are elucidated within the story “Los caballos de Abdera” (Las fuerzas extrañas). It is shown that even though the narrative treatment proposed by the Argentine author is not science fiction, it offers a model of the naturalization of fantastic events. In the first part we discuss the hermeneutical keys of this Lugonian reading, underscoring the flexibility of myth to adapt itself to the narrative paradigms of different ages. Using this plasticity of the mythical form, in the second part we analyze the process of familiarization through which the excessive use of technology in our daily lives has become normal. The purpose of this is to outline one of the recurring themes in science fiction: the invasion of alien beings.